A production and operations management study on McGraw Engineering - Funesto, Jim (College of Engineering, 2001)
McGraw Engineering is a manufacturing firm involved in the production of transformers. As a manufacturing company that aims to become a leading manufacturer and supplier of transformers in the country and the whole Asia by the year 2003, McGraw Engineering focuses on manufacturing quality, reliable, innovative and affordable products. The company produces two primary types of transformers - the Dry Type and the Oil-Immersed Sub-cooled Type. The company accomplishes the production of both types by employing large manual labor assisted by machines and tools throughout the nine-step process. Since the process for both types are generally the same, a process documentation encompassing both types was accomplished and evaluated. Forecasting the demand for transformers was facilitated through the use of the Decomposition of a Time Series (Multiplicative Seasonal Method), which was evaluated through tracking signals. The monthly forecasts for the year 2001 were used as basis for planning future capacity and workforce level requirements. Applying the concepts in Production and Operations Management, the group had identified three major problems: 1) Incorrect forecasting method used; 2) Low capacity of bottleneck; and 3) high undertime. The following recommendations were presented in addressing the problem areas mentioned: 1) use of Decomposition of a Time Series ad forecasting method instead of Naive Forecasting; 2) Acquisition of two additional rewinding machines to fill up the capacity gap based on the forecasted demand levels; and 3) the employment of 5 workers for workstation 1, and 1 worker each for workstations 2 and 3 to minimize undertime.